2018
DOI: 10.1016/j.ejphar.2018.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and serotonergic mechanisms in the modulation of pain: In vivo studies in human brain

Abstract: Here we review the literature assessing the roles of the brain dopaminergic and serotonergic systems in the modulation of pain as revealed by in vivo human studies using positron emission tomography. In healthy subjects, dopamine D/D receptor availability particularly in the striatum and serotonin 5-HT and 5-HT receptor availabilities in the cortex predict the subject's response to tonic experimental pain. High availability of dopamine D/D or serotonin 5-HT receptors is associated with high pain intensity, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 92 publications
2
25
0
Order By: Relevance
“…A decreased inhibitory tone exerted by endogenous dopamine-opioid system may be involved in the pathogenesis of BMS (Jääskeläinen, 2012;Jääskeläinen et al, 1997Jääskeläinen et al, , 2014Jääskeläinen et al, , 2001Jääskeläinen & Woda, 2017). The striatal dopamine system has been suggested to be involved in the modulation of pain (Jääskeläinen et al, 2014;Martikainen et al, 2018), possibly via triggering the endogenous opioid system (Jääskeläinen et al, 2014;Lamusuo et al, 2017). Furthermore, repetitive transcranial magnetic stimulation (rTMS) potentiates habituation of the BR reflex in healthy subjects (Lamusuo et al, 2017), by releasing dopamine and opioids (Lamusuo et al, 2017;Strafella, Paus, Barett, & Dagher, 2001;Strafella, Vanderwerf, & Sadikot, 2004) and simultaneously increasing pain detection thresholds (Jääskeläinen et al, 2014;Valmunen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decreased inhibitory tone exerted by endogenous dopamine-opioid system may be involved in the pathogenesis of BMS (Jääskeläinen, 2012;Jääskeläinen et al, 1997Jääskeläinen et al, , 2014Jääskeläinen et al, , 2001Jääskeläinen & Woda, 2017). The striatal dopamine system has been suggested to be involved in the modulation of pain (Jääskeläinen et al, 2014;Martikainen et al, 2018), possibly via triggering the endogenous opioid system (Jääskeläinen et al, 2014;Lamusuo et al, 2017). Furthermore, repetitive transcranial magnetic stimulation (rTMS) potentiates habituation of the BR reflex in healthy subjects (Lamusuo et al, 2017), by releasing dopamine and opioids (Lamusuo et al, 2017;Strafella, Paus, Barett, & Dagher, 2001;Strafella, Vanderwerf, & Sadikot, 2004) and simultaneously increasing pain detection thresholds (Jääskeläinen et al, 2014;Valmunen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Habituation of the BR, which is under dopaminergic control (Basso, Powers, & Evinger, 1996), has been found to be deficient in 20%-36% of patients (Forssell et al, 2002;Jääskeläinen et al, 1997), and PET studies have demonstrated low striatal dopamine levels in BMS (Hagelberg et al, 2003;Jääskeläinen et al, 2001). This finding may, in part, explain the perception of pain in BMS, as there are several lines of evidence that the dopaminergic system and striatal dopamine D2 receptors (DRD2) have an important role in central pain and its modulation (Hagelberg et al, 2003;Jääskeläinen et al, 2014;Martikainen, Hagelberg, Jääskeläinen, Hietala, & Pertovaara, 2018). DRD2 gene 957C<T polymorphism has been shown to influence both innocuous and noxious thermal detection thresholds in healthy subjects, being lowest in 957TT homozygotes (Jääskeläinen et al, 2014).…”
mentioning
confidence: 99%
“…Moreover, one study (7.6%) found that these patients had less paradoxical heat sensations than healthy controls, making them more accurate in defining whether they experience warm or cold sensations. 42 Only a few studies (30.8% of the studies) Full-text records included in qualitative synthesis (n = 13) *The abstract was only considered in Table 1 Studies 45,75,76 was related to higher HPT. 39 Specifically, the homozygous variant 957TT has been shown to be related to lower noxious thermal detection thresholds.…”
Section: Thermal Sensory Profile and Thermal Pain Sensitivitymentioning
confidence: 99%
“…Pain states have been associated with alterations in striatal dopamine D2R in both preclinical animal models and human imaging studies (Mitsi and Zachariou, 2016;Taylor et al, 2016). Human imaging studies have shown either increased or decreased striatal D2R receptor binding potentials using positron emission tomography in various pain states (Martikainen et al, 2018;Martikainen et al, 2015); however, these results could be due to changes in dopamine (DA) occupancy or altered D2R Bmax levels (or both). In addition, the direction and magnitude of changes in D2R binding potentials can rapidly change in chronic pain patients in response to acute pain challenge (DaSilva et al, 2017;Martikainen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Human imaging studies have shown either increased or decreased striatal D2R receptor binding potentials using positron emission tomography in various pain states (Martikainen et al, 2018;Martikainen et al, 2015); however, these results could be due to changes in dopamine (DA) occupancy or altered D2R Bmax levels (or both). In addition, the direction and magnitude of changes in D2R binding potentials can rapidly change in chronic pain patients in response to acute pain challenge (DaSilva et al, 2017;Martikainen et al, 2018). Moreover, human genetic studies have shown that polymorphism in the Drd2 gene is associated with baseline pain sensitivity, analgesic response to transcranial magnetic stimulation and likelihood of developing post-injury neuropathic pain (Jaaskelainen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%